AN ANALYSIS OF THE TENTH GRADE STUDENTS’ DIFFICULTIES ON ELLIPTICAL CONSTRUCTIONS AT MAN 1 KOTA TANGERANG SELATAN - Nita Astuti; Ikhfi - Imaniah (Universitas Muhammadiyah Tangerang, 2019)
An analysis of the tenth grade students’ difficulties on elliptical construction at MAN 1 Kota Tangerang Selatan become an issue in this study. The writers choose the 15 students randomly for sample. The method of the research is qualitative descriptive analysis where the data obtained from test, observation, and an interview. The primary data of the study is test about elliptical constructions. The test consists of 10 items in essay form of using so, too, either and neither in the sentences. The finding shows there are three difficulties of using elliptical constructions, namely 1) elliptical connector is 21 mistakes, 2) auxiliary is15 mistakes, and 3) omission the auxiliary is 12 mistakes. It can be concluded that the tenth grade students of science 2 are difficult in using elliptical construction. It is because they are still confuse to determine the using of so, too, either and neither in the sentences. The most factors that affect students’ difficulties are problems of meaning, form and form-meaning mapping.